2001
DOI: 10.1080/09712119.2001.9706751
|View full text |Cite
|
Sign up to set email alerts
|

Dry Matter, Crude Protein and Cell Wall Digestion of Total Plant, Leaves and Stems in Llano Buffelgrass (Cenchrus ciliaris)

Abstract: Foroughbackch, R., Ramirez, R.G., Hauad, L.A and Alba-Avila, J., GarciaCastillo, C.G. and Morales-Rodriguez, R. 2001

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In other experiments carried out in the same region, Ramirez et al (2001a;b) reported similar mean values (61.2%) in hybrid Nueces and in Common buffelgrass (64.4%). However, Foroughbackhch et al (2001) reported a mean value of 57% in the hybrid Llano. The ISDCW was higher in PI409228 (62%) and PI365731 (62%), whereas, PI409219 (46 %) was lower.…”
Section: Resultsmentioning
confidence: 94%
“…In other experiments carried out in the same region, Ramirez et al (2001a;b) reported similar mean values (61.2%) in hybrid Nueces and in Common buffelgrass (64.4%). However, Foroughbackhch et al (2001) reported a mean value of 57% in the hybrid Llano. The ISDCW was higher in PI409228 (62%) and PI365731 (62%), whereas, PI409219 (46 %) was lower.…”
Section: Resultsmentioning
confidence: 94%